Exploring Boron Neutron Capture Therapy for non-small cell lung cancer - Farías, Rubén Oscar (2014)
Boron Neutron Capture Therapy (BNCT) is a radiotherapy that combines biological targeting and high LET radiation. It consists in the enrichment of tumour with 10B and in the successive irradiation of the target with low energy neutrons producing charged particles that mainly cause non-repairable damages to the cells.The feasibility to treat Non Small Cells Lung Cancer (NSCLC) with BNCT was explored. This paper proposes a new approach to determine treatment plans, introducing the possibility to choose the irradiation start and duration to maximize the tumour dose. A Tumour Control Probability (TCP) suited for lung BNCT as well as other high dose radiotherapy schemes was also introduced.Treatment plans were evaluated in localized and disseminated lung tumours. Semi-ideal and real energy spectra beams were employed to assess the best energy range and the performance of non-tailored neutron sources for lung tumour treatments.The optimal neutron energy is within [500eV-3keV], lower than the 10keV suggested for the treatment of deep-seated tumours in the brain. TCPs higher than 0.6 and up to 0.95 are obtained for all cases.Conclusions drawn from [Suzuki etal., Int Canc Conf J 1 (4) (2012) 235-238] supporting the feasibility of BNCT for shallow lung tumours are confirmed, however discussions favouring the treatment of deeper lesions and disseminated disease are also opened. Since BNCT gives the possibility to deliver a safe and potentially effective treatment for NSCLC, it can be considered a suitable alternative for patients with few or no treatment options.